1989
DOI: 10.1209/0295-5075/8/7/002
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Effective Coupling Constants in “Finite” Grand Unification Theories in Curved Space-Time with Torsion

Abstract: PACS. 03.70 -Theory of quantized fields. PACS. 11.10 -Field theory. PACS. 04.50 -Unified field theories and other theories of gravitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The more general form of induced gravity action can be considered [10,11], but we restrict the couplings to be conformal. In the limit of ξ → 1 6 , this extended conformal coupling is reduced to the ordinary conformal coupling in Riemann space decoupled from the vector torsion.…”
Section: Conformal Couplings In Induced Gravitymentioning
confidence: 99%
“…The more general form of induced gravity action can be considered [10,11], but we restrict the couplings to be conformal. In the limit of ξ → 1 6 , this extended conformal coupling is reduced to the ordinary conformal coupling in Riemann space decoupled from the vector torsion.…”
Section: Conformal Couplings In Induced Gravitymentioning
confidence: 99%
“…The purpose of [13] is the investigation of the trace anomaly-induced dynamics of the conformal factor in four-dimensional quantum gravity. In [14] grand unification theories in curved spacetime with torsion are investigated. It is shown that in a strong gravitational field these effective coupling constants tend to conformal values or increase in an exponential way.…”
Section: Perturbative Calculations With Fluctuating Torsionmentioning
confidence: 99%
“…Theories with torsion also attract attention since torsion naturally arises in many approaches such as supergravity [17][18][19] and superstring [20][21][22] theories. One of the simplest extensions of the ECT is f (R) gravity with torsion [23,24], and, as shown in [24], torsion can play the role of DE and cause an accelerated expansion of the Universe.…”
Section: Introductionmentioning
confidence: 99%